2008
DOI: 10.1111/j.1872-034x.2008.00352.x
|View full text |Cite
|
Sign up to set email alerts
|

Griseofulvin, an oral antifungal agent, suppresses hepatitis C virus replication in vitro

Abstract: Our results suggest that griseofulvin may represent a new approach to the development of a novel therapy for HCV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
34
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 33 publications
0
34
0
Order By: Relevance
“…Nine of the compounds were active against both fungi within the same order of magnitude compared to griseofulvin (17,20,21,23,26,32,36,49, and 54).…”
mentioning
confidence: 96%
See 4 more Smart Citations
“…Nine of the compounds were active against both fungi within the same order of magnitude compared to griseofulvin (17,20,21,23,26,32,36,49, and 54).…”
mentioning
confidence: 96%
“…17−19 Several investigators have proposed tubulin as the main target for griseofulvin, although for mammalian cells this suggestion is not undisputed. 9,17,18,20,21,23,24 Recently, Panda et al 25 proposed two griseofulvin binding sites on tubulin using molecular docking studies and similar to Oda 21 reported that microtubule dynamics were disrupted by 1. Using the hepatitis C virus-1b cell culture system Huh7/Rep-Feo, Jin et al reported that G 2 /M phase arrest in infected cells was induced by griseofulvin (1).…”
mentioning
confidence: 99%
See 3 more Smart Citations